Cesium Carbonate Mediated Cyclization of Oxotryptamines with Allenoates: An Approach to Spiro[azepane-4,3′-indol]-2′(1′H)-ones - Yang, Ze-ren; Shi, Min (Synlett, 2021)
A new method was developed for the synthesis of spiro[azepane-4,3′-indol]-2′(1′H)-ones in yields of up to 96% with a broad substrate scope by using oxotryptamines as dual-nucleophilic reagents to react with allenoates in the presence of cesium carbonate under mild conditions. In accord with previous works and a deprotonation-tracing experiment, a plausible reaction mechanism is proposed.
Keywords: oxotryptamines; allenoates; spiro compounds; oxindoles; [4+3]-annulation